Enhancement of AGN in a protocluster at z=1.6 - Krishnan, Charutha; Hatch, Nina A.; Almaini, Omar; Kocevski, Dale; Cooke, Elizabeth A.; Hartley, William G.; Hasinger, Guenther; Maltby, David T.; Muldrew, Stuart I.; Simpson, Chris (Oxford University Press, 2017)
We investigate the prevalence of AGN in the high-redshift protocluster Cl 0218.3–0510 at z = 1.62. Using imaging from the Chandra X-ray Telescope, we find a large overdensity of AGN in the protocluster; a factor of 23±9 times the field density of AGN. Only half of this AGN overdensity is due to the overdensity of massive galaxies in the protocluster (a factor of 11±2), as we find that 17+6−5% of massive galaxies (M∗ > 1010M⊙) in the protocluster host an X-ray luminous AGN, compared to 8±1% in the field. This corresponds to an enhancement of AGN activity in massive protocluster galaxies by a factor of 2.1±0.7 at 1.6s significance. We also find that the AGN overdensity is centrally concentrated, located within 3 arcmin and most pronounced within 1 arcmin of the centre of the protocluster. Our results confirm that there is a reversal in the local anti-correlation between galaxy density and AGN activity, so there is an enhancement of AGN in high-redshift protoclusters. We compare the properties of AGN in the protocluster to the field and find no significant differences in the distributions of their stellar mass, X-ray luminosity, or hardness ratio. We therefore suggest that triggering mechanisms are similar in both environments, and that the mechanisms simply occur more frequently in denser environments.